Implementation of Character Education in Higher Education - Sakkir, Geminastiti; Jayadi, Karta; Sakkir, Rini Isnaeni (PT ARRUS Intelektual Indonesia, 2025)
This study explores the implementation of character education policies in higher education especially of first-semester students in the Fine Arts Education Study Program at Universitas Negeri Makassar. Using a qualitative descriptive approach, data were collected from 44 respondents through interviews and observations. The findings indicate that the implementation of character education policies in the learning process has a positive impact on the development of students’ character values, such as responsibility, honesty, discipline, tolerance, and cooperation. Students appreciate the approaches used in learning, such as discussions, reflections, case studies, and simulations, which help them understand and internalize these values. Furthermore, lecturers play a crucial role as facilitators and role models in instilling character values through interactive teaching methods.